Comparison of two cytoreductive regimens for αβ‐T‐cell‐depleted haploidentical HSCT in pediatric malignancies: Improved engraftment and outcome with TBI‐based regimen. Issue 2 (8th October 2017) - Jacoby, Elad; Varda‐Bloom, Nira; Goldstein, Gal; Hutt, Daphna; Churi, Chaim; Vernitsky, Helly; Toren, Amos; Bielorai, Bella
Abstract: Background: Graft manipulation using selective depletion of αβ‐T cells provides a source of haploidentical hematopoietic stem cell transplantation (haplo‐HSCT) enriched in effector cells. We report our experience implementing this haplo‐HSCT for high‐risk malignancies in pediatric patients focusing on the conditioning regimen. Procedure: We performed a retrospective study of patients who underwent T‐cell receptor αβ‐depleted haplo‐HSCT for high‐risk pediatric malignancies. Results: Eighteen patients underwent haplo‐HSCT using this method. The initial reduced‐toxicity chemotherapy‐based conditioning regimen was given to eight patients, and resulted in a high rate of graft rejections (six of eight patients). Thus, total body irradiation (TBI) based regimen was introduced in the following 10 patients and resulted in engraftment in all patients. Neutrophil and platelet engraftment were rapid (median time to engraft, 10 days and 12 days, respectively). Significant treatment‐related complications for both cohorts were all due to graft failure in patients receiving chemotherapy‐based conditioning, with a treatment‐related mortality rate of 17%. None of the patients developed hepatic sinusoidal‐obstruction syndrome, and no grade III–IV acute graft versus host disease (GVHD) was observed. The majority of patients were free of immunosuppression in the first 100 days post‐HSCT, and only two patients developed chronic GVHD. The cumulative incidence of relapse was 39%. Compared to patients conditioned with chemotherapy, patients conditioned with TBI had superior actuarial overall survival (66% vs. 37%, P = 0.05) and event‐free survival (61% vs. 33%, P = 0.04). Conclusions: A TBI‐based conditioning for haplo‐HSCT using αβ‐T‐cell depletion for malignant diseases ensured engraftment and resulted in acceptable outcomes.